The pathogenicity classification of PAH gene variants in the Iranian population. (June 2022) - Alibakhshi, Reza; Kazeminia, Mohsen; Moradi, Keivan
Abstract: Till now not many studies have been conducted to classify PAH gene variants according to American College of Medical Genetics and Genomics (ACMG-AMP) guidelines. The aim of this study was to collect all PAH gene variants reported among Iranian population and investigate their pathogenicity based on ACMG-AMP guidelines. Systematic collection of PAH gene variants, verification of variants, in silico analysis, and application of ACMG-AMP guidelines were the main steps in performing the present study. A total of 267 unique variants were identified; according to ACMG-AMP guidelines, 90, 40, 71, 14, and 52 variants were classified as pathogenic (P), likely pathogenic (LP), variant of uncertain significance (VUS), likely benign (LB), and benign (B), respectively. The need to pay more attention to synonymous and missense variants with low or no impact on protein function as well as intronic variants, whether they are deep or are close to intron/exon boundaries, was a highlight of this study. Due to the fact that few functional studies are performed on these variants, it is suggested that they be analyzed first using bioinformatics tools, and if positive results are obtained, then functional studies can be designed. Graphical Abstract: ga1 Highlights: PAH deficiency may have irreversible consequences including intellectual disability. In silico tools are useful in predicting deleterious effects of PAH gene variants. It is necessary to classify PAH gene variants according to ACMG-AMP guidelines. It should to pay more attention to synonymous and non-canonical intronic variants.